The influence of halal fashion, lifestyle, and brand image on Gen Z's hijab fashion preferences in Indonesia - Rahman, Riski; Indra , Indra (Journal of Islamic Economics Lariba, 2024)
IntroductionThe hijab is an important part of the daily lives of Muslim women in Indonesia. Several studies have been conducted regarding hijab preferences. However, research focusing on Generation Z is still limited. ObjectivesThis research aims to explain how fashion trends, lifestyle, and brand image influence hijab fashion preferences.MethodThis research uses quantitative research methods. The data collection technique used was a questionnaire for 104 respondents, with the criteria being Muslim women who were hijab consumers aged 11-26. The collected data was analyzed using the SEM-PLS approach.ResultsThe results of this research show that halal fashion, lifestyle, and brand image have a significant influence on hijab fashion preferences. Lifestyle variables have the most dominant influence.ImplicationsThe theoretical implications of this research indicate the need for a holistic approach to understanding Generation Z consumer behavior in the context of hijab fashion.Originality/NoveltyThis research shows the importance of collaboration between the fashion industry, religious institutions, and the government to develop regulations that support the growth of a high-quality hijab fashion industry in accordance with religious values.